Makna Mitsaqan Ghalizhan Perspektif Tafsir Al-Munir: Kajian atas Surah An-Nisa: 21 - Dahliana, Yeti; Wahab, Ahmad Ishom Pratama (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
Marriage is sunnatullah that applies to all of God's creatures. Marriage is a way chosen by God as a manner for his creatures to multiply and maintain the existence of their species. Marriage in Islam is defined as a sacred and great bond. The pledge of marriage bond established between husband and wife in the Qur'an is called misaqan galiza. In the Qur’an, the word misaqan galiza emerged three times. One meaning of the word misaqan galiza is the strong bond between spouses. This phrase was used in the Qur'an to illustrate how scary the relationship between husband and wife is even equated with the covenant between the Prophet and Allah. This study aims to utter the meaning of misaqan galiza in surah An-Nisa verse 21. The research method used is qualitative with the research type of library research. The data collection method used is documentation with descriptive-analytical data analysis techniques. The study results show that the meaning of misaqan galiza in Tafsir al-Munir is a great covenant because it involves Allah in it so that it causes afterlife consequences. Allah also commands to keep this promise wisely and if it is to be broken it is done in the best possible way.